2011
DOI: 10.1016/j.rbmo.2011.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Current opinion on use of luteinizing hormone supplementation in assisted reproduction therapy: an Asian perspective

Abstract: LH and FSH have complementary functions in ensuring optimal oocyte maturation and ovulation. In women undergoing assisted reproduction technology protocols with gonadotrophin-releasing hormone analogues, LH and FSH concentrations are reduced. While FSH use in assisted reproduction technology is well established, there is no published consensus on the need for exogenous LH in Asian patients. Having reviewed the concept of the LH therapeutic window and differences between recombinant human LH (r-HLH) and human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 53 publications
(71 reference statements)
0
40
0
Order By: Relevance
“…The poor outcome of COH includes increased age (above 35 years), poor ovarian reserve, poor response to previous ART cycles, genetic variations and hormonal status majorly LH, FSH, estradiol and anti-Mullerian hormone (AMH). [6] Overall, these studies suggest that LH supplementation could be beneficial for a particular sub-population, including older patients and poor responders. This might be due to the better ooctye quality resulting from a restored follicle at the end of stimulation in these ART patients.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The poor outcome of COH includes increased age (above 35 years), poor ovarian reserve, poor response to previous ART cycles, genetic variations and hormonal status majorly LH, FSH, estradiol and anti-Mullerian hormone (AMH). [6] Overall, these studies suggest that LH supplementation could be beneficial for a particular sub-population, including older patients and poor responders. This might be due to the better ooctye quality resulting from a restored follicle at the end of stimulation in these ART patients.…”
Section: Introductionmentioning
confidence: 94%
“…This is an area that warrants further research. [6] Studies have shown that serum LH levels should be between 1.2 IU/L and 5.0 IU/L,[8] for optimal development follicle in cycles where endogenous LH is suppressed. [619]…”
Section: Role Of Lh In Physiology: the Physiological Hormonal Interplaymentioning
confidence: 99%
See 3 more Smart Citations